(3GdQhGjJjf hGdhLgjfs - (3eMeO Hf eMeO GdbGVj GdaQGA GdMfHdj, CHj jYdj,J (B526 (3g` s
(3ChdgG (B:s
(3Ydjg hdcf EPG JQc KdGK UdhGJ dCfg jLhR Cf jchf THgI ONdJ Ydjg s
(3BNQgG (B:s
(3JXGgQ ef GQHY fSGFg HcdeI hGMOI abGd GfJf Ydi JXgQ Cei Ke YGO ef (B[ (3cdef (B] (3aYdjg caGQI hGMOI s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B23s
Keywords: (3Gdabg GdMfHdjs